2018
DOI: 10.1371/journal.pone.0206706
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hypoxia level of CT26 tumors during various stages of development and comparing different methods of hypoxia determination

Abstract: The aim of this study was to evaluate hypoxia level at various tumor developmental stages and to compare various methods of hypoxia evaluation in pre-clinical CT26 tumor model.Using three methods of hypoxia determination, we evaluated hypoxia levels during CT26 tumor development in BALB/c mice from day 4 till day 19, in 2–3 days intervals. Molecular method was based on the analysis of selected genes expression related to hypoxia (HIF1A, ANGPTL4, TGFB1, VEGFA, ERBB3, CA9) or specific for inflammation in hypoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…It is also interesting to observed that hypoxia seemed to be more severe in stage Ib/II tumors than in stage III tumors. Previously, a peak of tumor hypoxia at early stage of tumor development are also indicated in studies [45,46]. A possible explanation is the fast growth of tumor cells while the development of tumor blood vessels is inadequate at early stage.…”
Section: Discussionmentioning
confidence: 82%
“…It is also interesting to observed that hypoxia seemed to be more severe in stage Ib/II tumors than in stage III tumors. Previously, a peak of tumor hypoxia at early stage of tumor development are also indicated in studies [45,46]. A possible explanation is the fast growth of tumor cells while the development of tumor blood vessels is inadequate at early stage.…”
Section: Discussionmentioning
confidence: 82%
“…Untreated CRC tumors release CCL2 into the circulation, which is accompanied by an increase of CD115 hi monocytes in PB and strongly suggests that CD115 hi monocytes are mobilized by CCL2, most likely from the bone marrow, thereby con rming previous ndings [13]. By day 8 after tumor cell inoculation, blood levels of CCL2 and CD115 hi cells were signi cantly higher than in sham-treated mice without tumors, indicating that these effects are tumor speci c. CCL2 may be derived directly from CT26 and MC38 tumor cells, as observed in in vitro cultures [33][34][35], although this was not seen for CT26 cells by us (data not shown) or others [36], or induced in vivo under hypoxic conditions in tumor cells or other cells of the tumor microenvironment [37,38]. We cannot exclude that other chemokines such as CCL5, which can mobilize CD115 hi monocytes, are released as well [39].…”
Section: Discussionmentioning
confidence: 58%
“…The anti-tumor e ciencies of the liposomes were also studied on mice bearing C26 tumor models and monitored over a period of two months and compared with Caelyx ® [23]. It was shown that during the development of C26 tumor model in mice there were two peaks of hypoxia, rst at early stages of tumor formation and second peak during formation of necrotic areas due the fast-growing tumor cells [30]. Here we have injected the formulations at the early stage of tumor formation where the hypoxic microenvironment was taking place.…”
Section: Resultsmentioning
confidence: 99%